Pengaruh Gaya Kepemimpinan Berdasarkan Kepribadian Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di PT Al Andalus Nusantara Travel Surabaya - Rahma Indah Yunita; Ahmad Daengs GS; Harsono Teguh Santoso; Rina Dewi; Retno Susanti (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to determine the effect of leadership style and work environment on performance for marketing employees at PT. AL Andalus Nusantara Travel Surabaya. Where two independent variables and one dependent variable are proposed, namely the work environment and work stress act as independent variables and employee performance acts as the dependent variable. This research was conducted using a survey method of marketing employees at travel service companies and analyzed by regression. The first stage tested the validity and reliability of questions for each variable. The second stage, regressing the leadership style and work environment variables on employee performance. The results showed that the leadership style variable had a significant negative effect on employee performance and was rejected. As well as the work environment variable has a significant positive effect on employee performance is rejected. However, a work environment that is at a low to medium level will create good employee performance and will make employees worse if the time period is very long and excessive.